Genetic diversity of natural and restored api-api putih (Avicennia alba) populations in the west coast of Peninsular Malaysia - Lim, Kah Kheng; Neiva, Joao; M. Nazre; Serrao, Ester A. (Zibeline International Publishing, 2022)
A large tract of mangrove forest in Malaysia has been lost due to increased anthropogenic activities. Restorative practices of mangrove forest have been adopted nationwide to re-establish ecosystem services in combating coastal erosion. However, genetic considerations in local mangrove restoration practices are still far lacking despite the vast literature on their genetic diversity. To understand whether the restored mangroves can impact the genetic diversity distribution among natural populations, we used eight microsatellite markers to assess the genetic diversity of the Api-api putih (Avicennia alba) between the natural and restored populations along the west coast of Peninsular Malaysia. We found no difference in terms of genetic diversity between these populations. Two genetic clusters were detected among A. alba along the west coast based on Bayesian clustering and discriminant analysis of principal components (DAPC). The southwest monsoon current circulation that coincides the timing of seed dispersal of A. alba may explain such pattern of genetic differentiation. Despite the minimal genetic structure, our results suggest that seed sourcing from either population is viable for the local mangrove restoration programs in the future.